A Parametric Study of Vane and Air-jet Vortex Generators - Bray, Tim P. (Cranfield University, 1998)
An experimental parametric sturdy of vane and air-jet vortex generators in a turbulent boundary layer has been carried out. Experiments were carried out in two facilities, one with a free-stream velocity of 20 m/s and a boundary layer thickness (6) of 41.5 mm, and one in a high speed facility at free-stream Mach numbers of between 0.45 and 0.75 and a boundary layer thickness of 20 mm. Cross-stream data were measured at a number of downstream locations using a miniature five-hole pressure probe, such that local cross-stream velocity vectors could be derived. Streamwise vorticity was calculated using the velocity vector data. In the low speed study, vortex generator parameters were as follows: " Vane vortex generators: thin rectangular vanes with a vane aspect ratio of unity (2h/c = 1), free-stream velocity 20 m/s, incidence (cc = 10', 15', 18', 20'), height-to-boundary- layer- thickness-ratio (h/8 0.554,0.916,1.27,1.639), and strearnwise distance from the vortex generator (x/6 = 3.855,12.048,19.277,26.506). " Air-jet vortex generators: circular jet nozzles, free-stream velocity = 20 m/s, jet nozzle pitch and skew angles (cc, P= 30', 45', 60'), hole diameter-to-boundary-layer-thickness-ratio (D/5 = 0.098,0.193,0.289), jet-to-free-stream-velocity ratio (VR = 0.7,1.0,1.3,1.6,2.0), and strearnwise distance from the vortex generator (x/8 = 3.855,12.048,19.277,26.506). In the high-speed study, the vortex generator parameters were as follows: Vane vortex generators: thin rectangular vanes with an aspect ratio of unity, incidence ((X 1505 20'), he i ght-to- boundary- I ayer-th i ckne s s-rati o (h/8 = 0.75), strearnwise distance from the vortex generator (x/6 = 8.755 16.25,23.75), and free-stream Mach numbers of 0.45,0.6 and 0.75. Air-jet vortex generators: jet pitch ((x = 30', 45'), jet skew angle (P = 30', 45', 60'), hole diameter-to-boundary-layer-thickness-ratio (D/8 = 0.15,0.3), j et-to- free- strearn-ve loc ity ratio (VR = 1.6), and strearnwise distance from the vortex generator (x/6 = 8.75,16.25,23.75, 31.25), and free-stream Mach numbers of 0.50,0.6 and 0.75. Streamwise vorticity data from the experiment was used to generate prediction techniques that would allow the vorticity profiles, downstream of vane or air-jet vortex generators, to be predicted. Both techniques are based on the approximation of the experimental cross-stream vorticity data to Gaussian distributions of vorticity through the vortex centre. The techniques, which are empirically derived, are simple equations that give the peak vorticity and vortex radius based on the vortex generator parameters. Use of these descriptors allows the assembly of the Gaussian vorticity equation. Both techniques are compared with the experimental data set and were seen to produce peak vorticity results to within 12% and 20% (for the vanes and air-jets respectively), 15% for the radius of the vortex, and 15% and 20% in vortex circulation (for the vanes and air-jets respectively). The two simple prediction techniques allow good prediction of the vortex structure at extremely low computational effort.